2019
DOI: 10.1038/s41598-019-45636-8
|View full text |Cite|
|
Sign up to set email alerts
|

HNRNPA2/B1 is upregulated in endocrine-resistant LCC9 breast cancer cells and alters the miRNA transcriptome when overexpressed in MCF-7 cells

Abstract: MicroRNAs are dysregulated in breast cancer. Heterogeneous Nuclear Ribonucleoprotein A2/B1 (HNRNPA2/B1) is a reader of the N(6)-methyladenosine (m6A) mark in primary-miRNAs (pri-miRNAs) and promotes DROSHA processing to precursor-miRNAs (pre-miRNAs). We examined the expression of writers, readers, and erasers of m6A and report that HNRNPA2/B1 expression is higher in tamoxifen-resistant LCC9 breast cancer cells as compared to parental, tamoxifen-sensitive MCF-7 cells. To examine how increased expression of HNRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 245 publications
(251 reference statements)
1
63
0
Order By: Relevance
“…In LCC9 breast cancer cells resistant to endocrine, the upregulated HNRNPA2B1 seems to play a more complex role in miRNA transcriptome regulation. In detail, HNRNPA2B1 overexpressed in endocrine-resistant breast cancer cells reduces the sensitivity to 4-hydroxytamoxifen and fulvestrant by upregulating miR-1266-5p, miR-1268a, and miR-671-3p and downregulating miR-29a-3p, miR-29b-3p, and miR-222 [45]. Although previous studies have shown that HNRNPA2B1 can bind to pri-miRNAs and interact with DGCR8 for miRNA processing [39], the mechanism by which HNRNPA2B1 downregulates miRNA remains unclear.…”
Section: Roles Of M 6 a Methylation On Ncrnas In Cancer Micrornasmentioning
confidence: 99%
“…In LCC9 breast cancer cells resistant to endocrine, the upregulated HNRNPA2B1 seems to play a more complex role in miRNA transcriptome regulation. In detail, HNRNPA2B1 overexpressed in endocrine-resistant breast cancer cells reduces the sensitivity to 4-hydroxytamoxifen and fulvestrant by upregulating miR-1266-5p, miR-1268a, and miR-671-3p and downregulating miR-29a-3p, miR-29b-3p, and miR-222 [45]. Although previous studies have shown that HNRNPA2B1 can bind to pri-miRNAs and interact with DGCR8 for miRNA processing [39], the mechanism by which HNRNPA2B1 downregulates miRNA remains unclear.…”
Section: Roles Of M 6 a Methylation On Ncrnas In Cancer Micrornasmentioning
confidence: 99%
“…HNRNPA2/B1 overexpression promotes increases in m6A-modified miRNA levels by enhancing the process by which pri-miRNAs develop into pre-miRNAs and mature miRNAs. Moreover, pre-miRNAs and mature miRNAs can contribute to endocrine resistance by acting on targets or pathways [78]. Knocking down HNRNPA2/B1 can inhibit breast cancer cell proliferation and promote tumor cell apoptosis.…”
Section: M6a Modifications and Noncoding Rnasmentioning
confidence: 99%
“…METTL3 stabilizes YAP and Rho GTPase activating protein 5 (ARHGAP5) to induce cisplatin resistance in NSCLC and in GC [ 69 , 111 ]. HNRNPA2B1 is overexpressed in tamoxifen-resistant breast cancer and reduces 4-hydroxytamoxifen sensitivity [ 112 ]. In addition to METTL3 and METTL14, FTO and YTHDF2 are overexpressed in AML [ 26 , 27 , 113 , 114 ].…”
Section: Clinical Application Of M 6 a Methylationmentioning
confidence: 99%